2004
DOI: 10.1111/j.1365-2869.2004.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative utility of instruments for monitoring sleepiness‐related performance decrements in the operational environment

Abstract: SUMMAR Y As both military and commercial operations increasingly become continuous, 24-h-perday enterprises, the likelihood of operator errors or inefficiencies caused by sleep loss and/or circadian desynchrony also increases. Avoidance of such incidents requires the timely application of appropriate interventions -which, in turn, depend on the ability to measure and monitor the performance capacity of individuals in the operational environment. Several factors determine the potential suitability of candidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(128 citation statements)
references
References 23 publications
8
119
1
Order By: Relevance
“…According to this point of view, sleep deprivation effects on reaction time and trough-put in cognitively more loaded tasks would result from the monotony and lack of novelty that characterize these tasks. In contrast, tasks that are "too complex, too interesting, too variable and, above all, too short" would intrinsically encourage sleep-deprived people to apply compensatory efforts and to perform Balkin et al (2004) found that monotonous tests that demanded constant attention, like psychomotor vigilance tests, were most sensitive to partial sleep deprivation compared to tests involving higher cognitive load, like logical reasoning, problem-solving and decision-making, which were least sensitive (Balkin, Bliese, Belenky, Sing, Thorne, Thomas, et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…According to this point of view, sleep deprivation effects on reaction time and trough-put in cognitively more loaded tasks would result from the monotony and lack of novelty that characterize these tasks. In contrast, tasks that are "too complex, too interesting, too variable and, above all, too short" would intrinsically encourage sleep-deprived people to apply compensatory efforts and to perform Balkin et al (2004) found that monotonous tests that demanded constant attention, like psychomotor vigilance tests, were most sensitive to partial sleep deprivation compared to tests involving higher cognitive load, like logical reasoning, problem-solving and decision-making, which were least sensitive (Balkin, Bliese, Belenky, Sing, Thorne, Thomas, et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The PVT is known to be very sensitive to sustained attention deficits due to sleep deprivation. 18,19 Second, to examine the encoding and maintenance of information in WM, we administered a WM scanning task in which memory set items were presented serially ( Figure 1C). Using this procedure, it has previously been shown that the most recent two to three words presented before a probe are accessed more quickly and accurately because they remain in the focus of attention, whereas speed and accuracy of probe responses decline at later serial positions as items lose attentional activation.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with an earlier finding that performance on a driving simulator was predicted by sleep latency on a maintenance of wakefulness test. (31) The present finding pertaining to the PVT is a potentially important new contribution, because it indicates that a large volume of literature using PVT performance as an index of fatigue-related impairment (11,13,14,32) is relevant for driving performance-including a recently published biomathematical model for the prediction of fatigue and performance that was calibrated on PVT lapses. (25) Because of the between-groups design of the research study, the driving simulator scenarios (roads, routes, events, conditions, etc.)…”
Section: Ancillary Findingsmentioning
confidence: 99%